Wolf brother - Paver, Michelle (New York HarperCollins, 2004)
6,000 years in the past, twelve-year-old Torak and his guide, a wolf cub, set out on a dangerous journey to fulfill an oath the boy made to his dying father--to travel to the Mountain of the World Spirit seeking a way to destroy a demon-possessed bear that threatens all the clans.
First published: Great Britain : Orion Children Books.
5 up.
Keywords: Voyages and travels -- Fiction; Prehistoric peoples -- Fiction; Wolves -- Fiction; Demoniac possession -- Fiction; Bears -- Fiction